2021
DOI: 10.1161/circheartfailure.120.008410
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Angiotensin Receptor–Neprilysin Inhibition, Cardiovascular Biomarkers, and Cardiac Remodeling in Heart Failure With Reduced Ejection Fraction

Abstract: Background : Sacubitril/valsartan (S/V) treatment is associated with reverse cardiac remodeling and reductions in biomarkers reflecting ventricular wall stress and myocardial injury, such as N-terminal pro B-type natriuretic peptide (NT-proBNP), high-sensitivity cardiac troponin T (hs-cTnT) and soluble suppressor of tumorigenicity-2 (sST2). How longitudinal changes in these biomarkers analyzed collectively are associated with cardiac remodeling in patients with heart failure with reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“… 13 , 19 It is noteworthy that the lowest quintile for each biomarker identifies thresholds previously identified for risk stratification and cardiac remodelling for both NT-proBNP and hs-cTnT. 18 Given the strong and independent prognostic value of NT-proBNP and hs-cTnT when evaluated individually, a great potential exists in combining both for refining risk prediction in HF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 , 19 It is noteworthy that the lowest quintile for each biomarker identifies thresholds previously identified for risk stratification and cardiac remodelling for both NT-proBNP and hs-cTnT. 18 Given the strong and independent prognostic value of NT-proBNP and hs-cTnT when evaluated individually, a great potential exists in combining both for refining risk prediction in HF.…”
Section: Discussionmentioning
confidence: 99%
“…17 Similar to NT-proBNP, recent data have linked hs-cTnT concentrations to cardiac remodelling, where the two biomarkers have a unique correlation, with NT-proBNP change preceding that of hs-cTnT. 18 This leads to the hypothesis that increased myocardial stress (reflected in NT-proBNP concentrations) results in subsequent myocardial injury (reflected in hs-cTnT concentrations) ultimately culminating in adverse cardiac remodelling and worse prognosis. 13 , 19 It is noteworthy that the lowest quintile for each biomarker identifies thresholds previously identified for risk stratification and cardiac remodelling for both NT-proBNP and hs-cTnT.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the significant reduction in circulating NT-proBNP (and high-sensitivity cardiac troponin T) is correlated to the LA volume index reduction among HFrEF patients treated with ARNI. 121 Left atrial reverse remodelling can be considered an active player of the so-called 'complete left-sided reverse remodelling'. 16,48 This concept has been elucidated by trials testing the structural response to cardiac resynchronization therapy (CRT) (Table 4).…”
Section: Patients With Heart Failure (Stage C) Heart Failure With Red...mentioning
confidence: 99%
“…The effectiveness of sacubitril/valsartan therapy in patients with HFrEF has been appraised in many studies. The drug reduced plasma levels of NT-proBNP, high-sensitivity cardiac troponin T (hs-cTnT), and soluble suppressor of tumorigenicity 2 (sST2) in the patients, high levels of which reflect ventricular wall stress and myocardial injury ( Nougué et al, 2019 ; Murphy et al, 2021 ) ( Table 3 ). NT-proBNP level and left ventricular mass are positively correlated, and this fact is useful for identifying patients with cardiac hypertrophy ( Morillas et al, 2008 ; Kahveci et al, 2009 ).…”
Section: Mechanistic Roles Of Sacubitril/valsartan In Cardiac Remodelingmentioning
confidence: 99%